DEK protein level is a biomarker of CD138positive normal and malignant plasma cells - Caliskaner, Zihni Onur; Cakar, Turkan; Ozcelik, Emrah; Ozdilik, Ahmet; Kim, Annette S.; Dogan, Oner; Bosompem, Amma (Public Library Science, 2017)
Overexpression of DEK oncogene is associated with increased proliferation of carcinoma cells and it is observed in several solid tumors due to the amplification of the 6p22.3 chromosomal region where DEK locates. Although the same chromosomal amplification occurs in multiple myeloma (MM), a plasma cell neoplasm, whether the expression and the copy number of the DEK gene are affected in MM remains elusive. We show that despite the increased copy number in CD138(positive) MM cells (4 out of 41 MM samples), DEK mRNA expression was down-regulated compared with that in CD138(negative) bone marrow (BM) cells of the same patients (P< 0.0001). DEK protein was not detectable by immunohistochemistry (IHC) in CD138(positive) normal plasma cells or in malignant plasma cells of MM patients (n = 56) whereas it was widely expressed in normal and neoplastic B-cells. Stable knockdown or overexpression of DEK in CD138(positive) MM cell lines did not affect the proliferation and viability of the cells profoundly in the presence or absence of chemotherapeutic agent melphalan whereas knockdown of DEK moderately but significantly increased the expression level of CD138 (p< 0.01). Decreased DEK expression in plasma cells suggests a potential role of this gene in plasma cell development and lack of detectable DEK protein by IHC could be used as a biomarker for normal and malignant plasma cells.
Keywords: Multiple-Myeloma; Overexpression; Expression; Gene; Protooncogene; Inhibitor